A statistical quality control study on Del Monte Philippines, Inc. - Tan, Katherine; Cortez, Daniel Mark.; Hizon, Raphael Abraham IV. (Diliman, Quezon City College of Engineering, 2005)
At the onset of the semester, the group began to scout for companies that will allow for an Industrial Quality Control Study. The group was faced with a few alternatives, but it all boiled down to Del Monte Philippines Incorporated (DMPI). Then, the group started its initial plant visits at DMPI's plant location in Las Pinas. DMPI produces many kind of consumer products, and the 115 and 200 grams Stand-up-pouches Tomato Sauce were chosen as the product in focus. After knowing that the production of this SUP Tomato Sauce are done by about 13 Toll Packers, the group also visited one of its Toll Packers, Innovative Packing Industries Corporation (IPIC) in Valenzuela. Then, the group concentrated this study within the SUPs produced in IPIC, because they produce bulk of the SUP Tomato Sauce for DMPI. DMPI allowed the use of the Net Weight Conformance of 115 grams and 200 grams SUP Tomato Sauce observed and recorded during 2003 by the IPIC inspectors using SPC methods. The group also went around its plant facilities to know how their production operates. The group, during the whole study at Del Monte Philippines' Toll Packing Operations, focused on applying statistical tools to improving the company's quality especially on the net weight conformance of its tomato sauce stand-up-pouches (SUPs). The group started by documenting DMPI's operations, toll packing facilities, history, mission and vision and other information useful in analyzing the company's quality. The documentation focused on the equipment used, the company's production process, inspection process and methods of ensuring quality. Through this, the group wanted to record the company;s current practices and focus with respect to quality control. Problem analysis was then done to identify problem areas through observation, analysis of the system documented, and by recommendation of the company itself. As the main problem identification tools, the group was aided by Ishikawa diagrams, FMEA, Stream Diagnostic Chart. Consequently, the problems identified were the used as the focal point of analyses and recommendations. This was followed by cost analysis of the process to see how much is lost due to quality problems. The group discovered that this cost was significant due to the high volume involved an that the costs rely much on process variability.
The 2003 Net Weight Conformance Data were then subjected to Statistical Process Control (SPC) to determine of the monthly and yearly production of SUP Tomato Sauce were in control. The data points were rationally subdivided and plotted in monthly and yearly X and R charts. Some of the plotted were observed to be out of control limits, or simply put, out of statistical control. The initial control limits were then treated as trial control limits, Out of control points were eliminated by assuming that assignable causes were present. These points were identified as possible sources of external variability that have to be identified and taken out by the company through further study. New trials limits were recomputed and plotted which yielded no more out of control points. These new control limits and process parameters were then used for further process capability analyses. These new control limits were also used by the group as a standard of how current process would perform when it is in a state of statistical control. Process capability analysis was the next step done by the group in analyzing the data. Descriptive statistical tools, process capability ratios, histograms, inferential statistical tests for normality, central location, variability were used to examine the data. The results show that the process may not be capable to produce products within the set specification limits. The data was also found to be skewed to the right and not located at the target mean. The group suggested re-checking the specifications used and conducting experiments testing the machine sensitivity and the effect of variability on the means. The acceptance sampling plan was then evaluated by the group. It was found that the tests used have problems statistically and so the group suggested the use of fundamental SPC and acceptance sampling methods. Over-all, the group found that variability was the key component in improving the filling process .Reducing variability was found to reduce costs especially variable material costs. The group gave out specification limits based on the process' variability levels. A target was also given that would decrease costs and increase quality. The group also suggested a framework for accomplishing this goal.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Del Monte Philippines Incorporated; Plantations; Quality Control